Tapping Toulmin’s Sound Argument: EL Undergraduates’ Arguments Quality in the Research Discussion - Adianto Restu Wicaksono; Yazid Basthomi; Anik Nunuk Wulyani (Graduate School of Universitas Negeri Malang, 2023)
Rhetorical studies thus far have investigated the crucial rhetorical pattern in research discussion. However, those studies have not provided sufficient analyses on Toulmin’s model as a framework to determine arguments’ quality in research discussion. This study aims to investigate the ELE undergraduates’ arguments’ quality that manifested in research discussion. The finding of the study reveals undergraduates’ tend to form almost-complete arguments that consist of four Toulmin arguments elements, namely “Claim”, ”Data”, ”Warrant”, and “Back-Up” while “Qualifier” and “Rebuttal” are missing. This study provides interpretive elaboration of overall quality of the arguments and possible factors that led two elements being disregarded.